Deposição e caracterização de filmes finos de NbAIN por magnetron sputtering reativo - Carvalho, Renata Gomes (2016)
The objective of this work was to study NbAlN thin films and the influence of variation in the concentration of aluminum in the crystal structure, mechanical properties and oxidation resistance of these coatings. The thin films were deposited by reactive magnetron sputtering and characterized by Grazing Incidence X-ray Diffraction (GIXRD), Energy Dispersive Spectroscopy (EDS), Rutherford Backscattering Spectrometry (RBS), nanohardness analysis and oxidation tests at high temperatures. It was first necessary to define the deposition parameters of NbN thin films with δ-NbN phase (fcc). From this, NbAlN thin films were deposited and present at concentration of 10, 20 and 42 at% Al. The NbAlN crystalline phase obtained was the δ-NbN, however it was observed a shift of the peaks in the patterns obtained GIXRD of regions for larger angles for these samples, indicating the formation of a solid solution. The higher oxidation resistance temperature was 700° C for the sample with 42 in at% Al. From the SEM analysis it was possible to observe the surface of the film after oxidation, all films showed defects, however the amount of such defects was lower in samples with higher aluminum concentrations. The average hardness values obtained for thin films NbAlN was 25 GPa.